Comparative assessment of the copy number of satellite repeats in the genome of Triticeae species - P. Yu. Kroupin; A. I. Yurkina; A. A. Kocheshkova; D. S. Ulyanov; G. I. Karlov; M. G. Divashuk (Вавиловский журнал генетики и селекции)
Satellite repeats are a significant component of the genome of Triticeae and play a crucial role in the speciation. They are a valuable tool for studying these processes. Pseudoroegneria species play a special role among grasses, as they are considered putative donors of the St-genome in many polyploid species. The aim of this study was to compare the copy number of satellite repeats in the genomes of Triticeae species. Quantitative real-time PCR was applied to determine the copy numbers of 22 newly discovered satellite repeats revealed in the whole-genome sequences of Pseudoroegneria species and one additional repeat previously identified in the genome of Aegilops crassa. The study focused on seven species of Pseudoroegneria, three species of Thinopyrum, Elymus pendulinus, Ae. tauschii, Secale cereale, and Triticum aestivum. Based on the copy number level and coefficients of variation, we identified three groups of repeats: those with low variability between species (medium-copy CL82), those with medium variability (low- and medium-copy CL67, CL3, CL185, CL119, CL192, CL89, CL115, CL95, CL168), and those with high coefficients of variation (CL190, CL184, CL300, CL128, CL207, CL69, CL220, CL101, CL262, CL186, CL134, CL251, CL244). CL69 exhibited a specific high copy number in all Pseudoroegneria species, while CL101 was found in both Pseudoroegneria and Th. junceum, CL244 in Th. bessarabicum, CL184 in P. cognata and S. cereale. CL95, CL128, CL168, CL186, CL207, and CL300 exhibited higher copy numbers in P. cognata compared to other species; CL3, CL95, CL115, CL119, CL190, CL220, CL207, and CL300 in P. kosaninii; CL89 in P. libanotica; CL134 in P. geniculata. Our assessment of the copy number of new satellite repeats in the St-genome and the analysis of their amplification specificity between species can contribute to the molecular-genetic and chromosome markers used for evolutionary, phylogenetic, and population studies of Triticeae species.